Treatment effectiveness of PMTO for children's behavior problems in Iceland: Assessing parenting practices in a randomized controlled trial. Issue 6 (December 2013) - Sigmarsdóttir, Margrét; Degarmo, David S.; Forgatch, Marion S.; Guðmundsdóttir, Edda Vikar
<x xml:space="preserve">Abstract</x> Findings are presented from an Icelandic randomized control trial (RCT) evaluating parent management training – Oregon model (PMTO™), a parent training intervention designed to improve parenting practices and reduce child behavior problems. In a prior report from this effectiveness study that focused on child outcomes, children in the PMTO condition showed greater reductions in reported child adjustment problems relative to the comparison group. The present report focuses on observed parenting practices as the targeted outcome, with risk by treatment moderators also tested. It was hypothesized that mothers assigned to the PMTO condition would show greater gains in pre‐post parenting practices relative to controls. The sample was recruited from five municipalities throughout Iceland and included 102 participating families of children with behavior problems. Cases were referred by community professionals and randomly assigned to either PMTO (n = 51) or community services usually offered (n = 51). Child age ranged from 5 to 12 years; 73% were boys. Contrary to expectations, findings showed no main effects for changes in maternal parenting. However, evaluation of risk by treatment moderators showed greater gains in parenting practices for mothers who increased in depressed mood within the PMTO group relative to their counterparts in the comparison group. This finding suggests that PMTO prevented the expected damaging effects of depression on maternal parenting. Failure to find hypothesized main effects may indicate that there were some unobserved factors regarding the measurement and a need to further adapt the global observational procedures to Icelandic culture.